Exceptionally Low Arctic Stratospheric Ozone in Spring 2020 as Seen in the CAMS Reanalysis. Issue 23 (25th November 2020) - Inness, A.; Chabrillat, S.; Flemming, J.; Huijnen, V.; Langenrock, B.; Nicolas, J.; Polichtchouk, I.; Razinger, M.
Abstract: A reanalysis data set produced by the Copernicus Atmosphere Monitoring service (CAMS reanalysis, 2003 to present day) augmented by ERA5 data for the years before 2003 is used to describe the evolution of the 2020 Arctic ozone season and to compare it with years back to 1979. Ozone columns over large parts of the Arctic reached record low values in March and April 2020 because of an exceptionally strong, cold, and persistent Arctic polar vortex. Minimum ozone columns were below 250 DU for most of March and the first half of April, with the lowest values of 211 DU in the CAMS reanalysis found on 18 March. Such low values are extremely unusual for the Arctic. The previous years with similarly strong Arctic ozone depletion were 2011 and 1997 with minimum values of 232 and 217 DU, respectively. The performance of the CAMS ozone analysis is assessed by comparison with ozonesonde data and found to agree well with the independent observations. We find a clear sign of chemical ozone destruction with ozone severely depleted in a layer between 80 and 50 hPa in late March and early April when partial pressure values below 2 mPa were observed. Profiles from the limb sounders Atmospheric Chemistry Experiment‐Fourier Transform Spectrometer (ACE‐FTS) and Microwave Limb Sounder (MLS) show clear signs of chlorine activation and the presence of polar stratospheric clouds. Monthly mean ozone columns in March 2020 were up to 180 DU or 40% lower than the CAMS climatology (2003–2019) while values for 2011 and 1997 were lower by 31% and 35%, respectively. Plain Language Summary: The stratosphere is the layer of the atmosphere between about 15 and 50 km where most of the ozone resides. Usually, Arctic ozone reaches maximum values in the stratosphere during boreal spring. However, in spring 2020 the Arctic stratosphere was exceptionally cold, and ozone transport from the midlatitudes was inhibited. Because of the low temperatures, polar stratospheric clouds could form over the Arctic region and lead to stratospheric ozone destruction. This led to record low ozone columns in the Arctic at the end of March and the beginning of April 2020, with minimum values of 211 DU. This is lower than in 1997 and 2011, the previous two years that had exceptionally low ozone columns over the Arctic during spring. In spring 2020, the Arctic ozone layer showed clear signs of chemical ozone depletion with ozone almost completely destroyed in a layer around 18 km in a way that is usually only seen over the Antarctic during the austral spring, when the ozone hole forms. Key Points: Arctic ozone columns in spring 2020 were the lowest since 1979 because the Arctic polar vortex was unusually strong, cold, and long lasting We see evidence of chlorine activation and the presence of polar stratospheric clouds over the Arctic in March 2020 The CAMS reanalysis captures the 2020 Arctic stratospheric ozone well